Co-creation and learning : concepts and cases - Akhilesh, K. B. (Springer, 2017)
This book introduces readers to co-creation -- a complex, value-based, context-driven and collaborative effort to develop new paradigms, products and services to satisfy human wants. Co-creation is built not only around the perceptions of challenges, cause-and-effect relationships and constraints, but also around available alternatives for dealing with or overcoming those challenges. Co-creation is not about transferring or outsourcing activities, and neither is it about the customization of products and services. This book explains the emergence of the co-creation approach. It describes various models of value creation, as well as different stages and the contract process involved in co-creation. It also explores different types of learning and learning techniques, and how co-creation impacts the learning process. The book allows practitioners and policymakers to understand the processes involved in implementing co-creation in any organization, while also presenting case studies to show how to apply the relevant concepts in their day-to-day activities.
Keywords: New products.; New business enterprises.; Technological innovations -- Management.; elektronické knihy; electronic books